Pengembangan Media Pembelajaran Flash Berbasis Joyfull Learning bagi Siswa Kelas IV SD - Azhar, Arry Patriasurya; Rahayu, Zaenab Fuji (Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine the feasibility of flash learning media products based on joyful learning for fourth grade students, namely science learning with the subject of